The Role of Christian Religious Education in Improving Work Discipline of POLRI Members in the Southeast Minahasa POLRES SATLANTAS - Bokau, Maya Imelda Sari; Mokalu, Valentino Reykliv (CV. Rayyan Dwi Bharata, 2024)
Weakening the level of discipline of POLRI members will affect their main duties in line with Law no. 2 of 2002 which was implemented. The condition of weakening discipline of POLRI members is currently starting to be frequently discussed and questioned, so there needs to be reform that must be implemented in law, so that it can provide firmness for POLRI members who are negligent in carrying out discipline. Efforts from Christian religious education are a complex contribution and can be used as a tool to guide members of the National Police in forming work discipline, so that the self-image of members of the National Police does not fall just because of disciplinary problems that have been acquired during their education and in carrying out their service. The results obtained in this research are that there is no work discipline from the members of the SATLANTAS Police at the Southeast Minahasa POLRES. There is no standard PAK role in improving the discipline of the SATLANTAS Police at the Southeast Minahasa POLRES, because the PAK program is not implemented.